Evaluation of SNR-based GNSS-reflectometry altimetric precision by a height displacement tool - Selbesoglu, Mahmut Oguz; Karabulut, Mustafa Fahri; Aykut, Nedim Onur; Akpinar, Burak (ELSEVIER SCI LTD, 2022)
Global Navigation Satellite System Reflectometry (GNSS-R) technique is an approach that has been used in the last few years and produces effective results to estimate important climate change parameters such as snow thickness, sea level, forest biomass, growth of vegetation. In this study, the GNSS-R technique height determination accuracy was evaluated by using a vertical displacement tool that allows shifting the receiver height and measure within 1 mm accuracy. The main purpose is to investigate the accuracy of the GNSS-R technique to monitor vertical displacements of buildings which surfaces is smooth and the signal strength is high. For this purpose, height of the GNSS antenna was set to 3 heights with a 5 cm interval on the displacement tool. The signals was analyzed based on dominant signal reflection effect frequency of Signal to Noise Ratio (SNR) data and heights were determined by Lomb-Scargle Periodogram (LSP) method. According to the results, GNSS-R technique provide sufficient accuracy with a 0.51 cm RMSE for smooth surfaces. (C) 2022 COSPAR. Published by Elsevier B.V. All rights reserved.
Keywords: GNSS; SNR; Reflected signals; Reflectometry; Signal analyzes; Displacement; GPS; DEFORMATION; SYSTEM; DELAYS; Engineering; Astronomy & Astrophysics; Geology; Meteorology & Atmospheric Sciences